The Effectiveness of Collaborative Strategic Reading (CSR) and Cooperative-Discussion-Question (Coop-Dis-Q) in Teaching Reading Comprehension - Walidaini, Lulu; Mujiyanto, Januarius; Warsono, Warsono (English Education Journal, 2021)
This study aims to measure the effectiveness of collaborative strategic reading (CSR) and cooperative-discussion-question (Coop-Dis-Q) strategies in teaching reading comprehension students with impulsive and reflective cognitive learning styles. To improve students' reading comprehension skills, the researcher wants to study both strategies. This research used 2x2 factorial experimental designs. The subjects were XI MIPA 1 and XI MIPA 4 classes of SMAN 1 Pangkah, Tegal Regency. They were divided into two groups, and categorized impulsive and reflective students. The instruments used were test, pre-test, post-test, and questionnaires. This research indicated that collaborative strategic reading (CSR) was more effective than cooperative-discussion-question (Coop-Dis-Q) to students with impulsive cognitive learning styles. Simultaneously, there was no significant difference between the students who were taught by using collaborative strategic reading (CSR) and those taught by cooperative-discussion-question (Coop-Dis-Q) with reflective cognitive learning style. It meant that CSR was more effective for the students with impulsive cognitive learning styles, while Coop-Dis-Q was effective for the students with reflective cognitive learning styles. Based on the findings, the researchers concludes that CSR and Coop-Dis-Q appeared to improve the students' reading comprehension skills for both impulsive and reflective students.